Biology of mood & anxiety disorders (Biomed Central, 2011)
An open access peer-reviewed journal that publishes highly innovative basic, translational, and clinical research that advances our understanding of the pathophysiology of mood and anxiety disorders. The journal welcomes research in all areas relevant to the disorders at the level of their underlying mechanisms.